Incidence and treatment patterns of complicated bone metastases in a population-based radiotherapy program. Issue 3 (March 2016) - Tiwana, Manpreet S.; Barnes, Mark; Yurkowski, Emily; Roden, Kelsey; Olson, Robert A.
Abstract: Introduction: There is abundant evidence in support of single fraction (SF) radiation therapy (RT) for uncomplicated bone metastases (BoM). We sought to determine the proportion of BoM that is complicated in a population-based RT program in order to act as a potential guide for assessing SFRT utilization rates. Materials and methods: A total of 3200 RT courses were prescribed to 1880 consecutive patients diagnosed with BoM in 2013. Associations between choice of RT fractionation and BoM characterization, whether complicated or not, were assessed with logistic regression. Results: The incidence of complicated BoM was 34.4%, resulting most often from adverse features of actual pathological fracture (42.1%), and neurological compromise (36.3%). Complicated BoM were most common in lung cancers (24.2%) and in the spine (68.5%), followed by extremity (15.2%) and pelvis (14.4%). SFRT was prescribed less commonly in complicated versus un-complicated BoM (39.4% vs. 70.4%; p < 0.001), which was confirmed on multivariable analysis (OR 0.32; 95% CI 0.28–0.61; p < 0.001). Conclusions: This study found that 34.4% of BoM are complicated by fracture, or neurological compromise (i.e. 65.6% were un-complicated), and that they were less likely to receive SFRT. A reasonable benchmark for SFRT utilization should be at least 60%.